Multiangle dynamic light scattering analysis using amodified Chahine method - Liu, Xiaoyan (2012)
Multiangle dynamic light scattering (MDLS) is used to determine particle size distributions (PSDs). The angular intensity weighting coefficients used in the inversion of the PSD data affect dramatically the PSD recovered. Noise in the weighting factors gives rise to poor PSD results. A modified Chahine method, which is insensitive to the noise of the weighting coefficients, is developed for estimating the PSD from MDLS. The method was evaluated through simulated examples that involved unimodal and bimodal PSDs of different shapes and employed for estimating two bimodal PSDs obtained by mixing two standard polystyrene latexes. For comparison, all examples were also analyzed using a nonnegatively-constrained Tikhonov regularization technique typically used for inverting ill-conditioned linear problems. The PSDs estimated by the proposed modified Chahine method were more accurate than those obtained by the Tikhonov technique.